Manhaj Ta’līmil Al Lughah Al ‘Arabiyyah li Al Indūnīsiyyīn Al Mubtadiīn bi Istikhdām Al Kalimāt Al Indūnīsiyyah dzāt Ashlin ‘Arabiy fī (KBBI) -Harf A Namūdzajan- - Intan Maulisa; Evi Khulwati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
هدفت هذه الدراسة إلى كشف الكلمات الإندونيسية التي لها أصل عربي، ثم تكوين المنهج المناسب لتعليم اللغة العربية للمبتدئين الإندونيسيين باستخدام تلك الكلمات. وإن منهج هذا البحث هو المنهج الوصفي التحليلي الذي مهد للباحثة كشف الكلمات الإندونيسية التي لها أصل عربي ثم الاستفادة منها في تكوين منهج تعليم اللغة العربية للطلاب المبتدئين. ونتائج البحث تتلخص فيما يلي: 1) وجود الكلمات الإندونيسية ذات أصل عربي في معجم اللغة الإندونيسية الكبير (KBBI) وعددها وصل نحو مئة أربع وخمسين(124) كلمة من حرف A. 2) أنه من خلال هذه الكلمات الإندونيسية التي لها أصل عربي يمكن تيسير عملية التعلم والتعليم للمبتدئين الإندونيسيين. 3) وأنه يمكن تكوين المنهج المناسب باستخدام تلك الكلمات الإندونيسية التي لها أصل عربي لتعليم اللغة العربية للطلاب الإندونيسيين المبتدئين. This study aims to express Indonesian words originating from Arabic, then form an appropriate curriculum for teaching Arabic for Indonesian beginner learners by using these words. This study adopts a descriptive-analytic method, where the method paves the way for writers to uncover the Indonesian vocabulary derived from Arabic, which then from the vocabulary can be compiled an appropriate curriculum for teaching Arabic for Indonesian beginners. The results of the study are summarized as follows: 1) The existence of Indonesian vocabulary from Arabic in the Big Indonesian Dictionary (KBBI) which amounts to around one hundred and five (124) vocabularies from letters A. 2) Through the Indonesian vocabulary, the learning and teaching process can make it easier for Indonesian beginners. 3) That an appropriate curriculum can be formed using Indonesian vocabulary derived from Arabic, to teach Arabic to Indonesian beginner students.